MOTIVASI MAHASISWI UNTUK MENIKAH PADA MASA PERKULIAHAN (STUDI KASUS MAHASISWI PROGRAM STUDI PENDIDIKAN AGAMA ISLAM ANGKATAN 2016 UNIVERSITAS ISLAM MALANG) - Ela Yuniar; Mohammad Afifulloh; Devi Wahyu Ertanti (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The research in this thesis is motivated by the number of female students who have been married during the lecture. Of married students who are still able to carry out their duties as students properly. Researchers want to know about the Motivation of Students to Get Married in College (Case Study of Islamic Education Study Program Class 2016 Universitas Islam Malang). This research uses a qualitative approach to the type of case study research. The results of the study indicate that intrinsic motivation or motivation that comes from within a student is to avoid immorality and adultery, the desire to get married, want to have an encouragement to live and study. While extrinsic motivation or motivation that comes from within a student is to get the blessing and support from parents, belief in her husband, and environmental support of the local community. Having both roles, both as female students and as a wife, makes them to manage their time well, carrying out activities according to their schedule. The perceived obstacle in getting married during the lecture is due to the pregnancy factor which makes the lecture a little hampered but does not make it leave the lecture.